2017
DOI: 10.1021/jacs.7b02569
|View full text |Cite
|
Sign up to set email alerts
|

Merging Photoredox with 1,2-Metallate Rearrangements: The Photochemical Alkylation of Vinyl Boronate Complexes

Abstract: Vinyl boronates react with electron-deficient alkyl iodides in the presence of visible light to give boronic esters in which two new C-C bonds have been created. The reaction occurs by radical addition of an electron-deficient alkyl radical to the vinyl boronate followed by electron transfer with another molecule of alkyl iodide, continuing the chain, and triggering a 1,2-metalate rearrangement. In a number of cases, the use of a photoredox catalyst enhances yields significantly. The scope of the radical precu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
83
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(86 citation statements)
references
References 61 publications
0
83
2
1
Order By: Relevance
“…The use of the more reducing photocatalyst Ir(ppy) 3 gave similar results (entry 5). In contrast to the photochemical three‐component alkylation of vinyl boronate complexes, we observed that the use of a photocatalyst was crucial for obtaining high yields in this reaction (compare entries 4 and 6). A control experiment carried out in the dark did not give any product (entry 7), showing the photochemical nature of this transformation.…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation
“…The use of the more reducing photocatalyst Ir(ppy) 3 gave similar results (entry 5). In contrast to the photochemical three‐component alkylation of vinyl boronate complexes, we observed that the use of a photocatalyst was crucial for obtaining high yields in this reaction (compare entries 4 and 6). A control experiment carried out in the dark did not give any product (entry 7), showing the photochemical nature of this transformation.…”
Section: Methodsmentioning
confidence: 91%
“…However, in control experiments we found that neither light nor the photocatalyst were required for the transformation. Furthermore, addition of the radical inhibitor 1,1‐diphenylethylene had no effect on the reaction outcome (see Supporting Information–3.5 for details), ruling out a possible electron‐transfer initiated radical chain process and supporting a polar S N 2‐like pathway. The nucleophilic reactivity of indole‐derived borates generated from difficult‐to‐handle trialkyl boranes has been described, however the difficulties in accessing enantioenriched chiral boranes has prevented the use of this methodology for the synthesis of chiral compounds in enantioenriched form.…”
Section: Methodsmentioning
confidence: 99%
“…[6] In particular, the rearrangement of vinylboronate complexes for the generation of alkylboronates has attracted considerable attention from many research groups ( Figure 1a). [8a] In 2017, three groups independently extended this elegant chemistry to the radical-polar crossover process using vinyl boronate complexes and alkyl halides triggered by Et 3 B/air, [9] visible light, [10] or nickel catalysts. [7] Half ac entury later, Morken et al reported an important breakthrough for 1,2-alkyl/aryl migration [8] through carbopallada-tion of vinylboronate complexes with different coupling partners.…”
mentioning
confidence: 99%
“…[7] Thus the Nicatalyzed hydrocarbonation of both terminal and internal alkenes shows linear selectivity (Scheme 1b). [9] While some of the products might be accessed by alternative methods such as the hydroboration of styrenes, [10] cross-couplings or reductive couplings of a-halo boronic esters, [11] difunctionalization of alkenyl boronates through 1,2metalate shifts, [12] as well as three-component couplings of terminal alkynes,p inacolborane,a nd aryl halides, [1j] our method offers ample advantages such as anew disconnection, wide reagent availability,m ild conditions,b road scope,a nd high regioselectivity. [2e-g, 8] Thea ryl group cannot be easily removed and offers limited opportunities for further functionalization.…”
mentioning
confidence: 99%